AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 36: NOBEL PRIZE LAUREATES IN PHYSICS FOR 1995-1999 - M.I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. Implementation of brief analytical review of the distinguished scientific achievements of the world scientists-physicists, awarded the Nobel Prize in physics for period 1995-1999. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information of world level in area of modern theoretical and experimental physics. Results. The brief analytical review of the scientific openings and distinguished achievements of scientists-physicists is resulted in area of modern physical and technical problems which were marked the Nobel bonuses on physics for period 1995-1999. Originality. Systematization is executed with exposition in the short concentrated form of the known scientific and technical materials, devoted opening of tau-lepton, experimental discovery of electronic neutrino, opening of superfluidity of liquid helium-3, creation of methods of cooling and «capture» of atoms by a laser ray, opening of new form of quantum liquid with excitations of fractional electric charge and clearing up of quantum structure of electroweak interactions of elementary particles scientists-physicists. Practical value. Popularization and deepening of scientific and technical knowledges for students, engineer and technical specialists and research workers in area of modern theoretical and experimental physics, extending their scientific range of interests and further development of scientific and technical progress in human society.